FREQUENCY AND CRITERIA OF DEGREE OF EXPRESSIVENESS NOT DIFFERENTIATED DYSPLASIA A CONNECTIVE TISSUE AT LEІOMYOMA A UTERUS AT WOMEN OF REPRODUCTIVE AGE - Запорожченко, М.Б. (World of Medicine and Biology, 2014)
The work purpose was studying of frequency and criteria of degree of expressiveness not differentiated dysplasia a connective tissue at leіomyoma a uterus at women of reproductive age. 300 women of reproductive age on presence of clinical signs not differentiated dysplasia a connective tissue are surveyed. Defined the maintenance of the general hydroxy-proline and glycosoaminoglicans. On the average signs not differentiated dysplasia a connective tissue are found in 26,3 % of women with leіomyoma a uterus. At presence leіomyoma proliferativ type concentration of the general hydroxy-proline reached 101,9±6,1 mg/d that was essential more (р